Study of Mechanical, Physical, and Morphological Properties of Composites Used in Civil Construction - Cardoso, Adriano Pereira; Bassani, Felipe Nakamura; Cardoso , Flávia Aparecida Reitz; Herek, Luciana Cristina Soto; Paccola, Edneia Aparecida de Souza (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The search for sustainable materials in the construction sector is crucial due to its significant environmental impact. Composite material technology emerges as a solution but faces technological challenges in formulating and stabilizing mixtures to minimize environmental impact. This study investigated the environmental behavior of composites made from recycled wood and plastic materials directly sourced from the industry. Three compositions were tested: 100% recycled plastics, 70% recycled wood and 30% recycled plastic, and 70% recycled wood and 30% virgin PVC. After machining to comply with mechanical testing standards, the materials underwent tensile and impact tests. Statistical analyses identified the most resistant samples for civil construction applications. Morphological analysis revealed voids and agglomerates in the compositions, as well as the distribution and compatibility of the filler materials. The water absorption test determined that the composition made entirely of recycled plastics performed best due to its hydrophobic nature, in terms of mechanical, physical, and morphological parameters. This study highlights the feasibility of sustainable composites in construction and the importance of proper material selection to achieve the desired properties.